Certified simulation of IGBT transistor in solar model (Sebha University Conference Proceedings, 2024)
Power electronics systems have gradually gained an important place in a wide range of industrial applications, and recent research has led to an effort to improve the reliability of electronic power systems to comply with more stringent constraints on safety, cost, and reliability. Electronic power systems consist of various components, including power semiconductor devices, which are one of the most fault-prone components of electronic circuits, and play a major role in the output and reliability of overall electronic power systems. One of these elements is an insulated-gate bipolar transistor (IGBT), and temperature stress is a major stress factor that leads to failure of IGBT modules. In this paper, the failure mechanisms and reliability of the IGBT transistor in solar energy applications were studied, and simulations were conducted to evaluate the behavior of the transistor under different operating conditions, such as varying temperatures depending on solar radiation throughout the day, and voltage levels.